Clinical application value of intracavitary PRP infusion combined with IVF-FET in patients with chronic endometritis - ZHANG Xiaotong; HAO Xiaoyuan; FANG Rui; HU Shuyao; MA Linkun; ZHAO Yaqi; HAN Wei (Zhongguo shuxue zazhi)
[Objective] To evaluate the clinical application value of intrauterine perfusion with platelet-rich plasma (PRP) combined with in vitro fertilization-frozen-thawed embryo transfer (IVF-FET) in patients with chronic endometritis (CE). [Methods] A randomized controlled trial (RCT) was conducted, enrolling 60 CE patients undergoing artificial cycle frozen embryo transfer at our hospital from January 2022 to January 2024. Participants were randomly divided into three groups: Group A (routine frozen embryo transfer, n=20), Group B (routine frozen embryo transfer + one PRP intrauterine perfusion, n=20), and Group C (routine frozen embryo transfer + two PRP intrauterine perfusions, n=20). Endometrial thickness during the transformation and transplantation phases, uterine artery pulsatility index (PI), resistance index (RI), systolic peak velocity/end-diastolic velocity (S/D) ratio during transplantation, serum levels of IL-2, IL-4, IL-6, IL-10, and TNF-α during transplantation, as well as biochemical pregnancy rate, clinical pregnancy rate, live birth rate, and early miscarriage rate were compared across groups. [Results] No significant differences in endometrial thickness were observed among the three groups during the transformation phase (P>0.05). During the transplantation phase, endometrial thickness in Groups C and B was significantly higher than in Group A[9.54 (8.96-10.22) and 8.90 (8.34-9.72) vs 8.37 (7.89-8.75) mm, P<0.05], with Group C showing greater thickness than Group B (Z=3.733, P<0.05). Endometrial thickness in Groups C and B during transplantation was significantly increased compared to their respective transformation phases (Z=2.191, 2.462; P<0.05). Groups C and B exhibited lower PI, RI, and S/D values than Group A[PI:1.87 (1.77-1.97), 1.94 (1.88-2.15) vs 2.43 (2.35-2.49); RI:0.75 (0.73-0.77), 0.78 (0.75-0.81) vs 0.84 (0.83-0.86); S/D:2.61 (2.33-3.42), 3.01 (2.20-3.93) vs 3.72 (3.06-4.49); P<0.05]. Group C demonstrated lower PI and RI than Group B (P<0.05). IL-2 levels in Groups C and B were higher than in Group A[3.88 (2.71-5.01), 3.59 (2.73-4.38) vs 3.16 (2.11-3.25) ng/L, P<0.05], while IL-4, IL-6, IL-10, and TNF-α levels were significantly lower (IL-4: Z=1.428, 2.421; IL-6: Z=1.754, 2.435; IL-10: Z=1.754, 2.854; TNF-α: Z=1.961, 1.765; P<0.05). Group C had lower IL-6 levels than Group B (Z=3.976, P<0.05). Biochemical pregnancy rate, clinical pregnancy rate, and live birth rate in Group C were significantly higher than in Group A (75% vs 40%, 70% vs 35%, 60% vs 20%, P<0.05). No significant differences in early miscarriage rates were observed among the groups (χ2=3.750, P>0.05). [Conclusion] Intrauterine autologous PRP perfusion in CE patients enhances pregnancy and live birth rates, improves pregnancy outcomes post-FET, and demonstrates superior efficacy in endometrial repair and receptivity with two PRP perfusions compared to a single perfusion. This provides a safe and effective therapeutic option for optimizing outcomes in CE patients with prior implantation failure.